Community-Based Peer-Led Intervention for Healthy Ageing and Evaluation of the ‘HAPPY' Program - Merchant, Reshma A.; Tsoi, C.T.; Tan, W.M.; Lau, W.; Sandrasageran, S.; Arai, H. (The Journal of nutrition, health & aging, 2021)
Population ageing impacts many areas of society from health and social care cost to housing and future workforce, and whole-of-society approach is required to promote healthy ageing. The Decade of Healthy Ageing report has called upon multi-sectoral collaboration to promote age-friendly communities. The Healthy Ageing Promotion Program for You (HAPPY) is a community-based dual-task exercise program for older adults led by health coaches (HC) or trained volunteers (HAPPY leaders) to promote healthy ageing. The primary objective was to observe improvement in cognition. The secondary objective was to observe improvement in frailty status, functional status, perceived health and reduction of social isolation. We also aim to evaluate the effectiveness and describe the implementation of the HAPPY program. To engage older adults with prefrailty, frailty and/or cognitive impairment in dual-task exercise program. Recruitment and publicity were through country-wide multisectoral collaboration. Community setting More than 700 older adults participated in ≥ 50 different sites including senior activity centres. Five hundred and sixty-nine participants attended phase 1 screening. Pre-frail or frail ambulant participants or those with underlying cognitive impairment were invited to participate in phase 2 screening. Among them 296 participants enrolled in phase 2 with 66.6% follow up rate at 3 months. Phase 1 and 2 screening consisted of screening for frailty (FRAIL), cognition (Montreal Cognitive Assessment [MoCA]), falls, vision, grip strength, perceived health (EuroQol vertical visual analogue scale), depression (geriatric depression scale), social network (6-item Lubben Social Network Scale), gait speed and physical function (Short physical performance battery [SPPB]). HC led 61.7% of the participants, and HAPPY was conducted twice weekly for 64% of the participants. There was significant improvement in the MoCA scores both in the HC and HAPPY leaders' led groups. Overall physical function, chair-stand and balance domain improved significantly especially in the groups led by HC and those participating in twice-weekly exercises. There was significant improvement in perceived health, reduction in social isolation, improvement in frailty status and reduction of falls at 3 months. Community embedded peer-led program to promote healthy ageing like HAPPY can improve cognition, physical function, and frailty status, reduce social isolation, and improve perceived health. It takes a “village” to promote healthy ageing, and the need to have a life course approach to healthy longevity which must involve local government and ministerial organisations, non-profit organisations, industries, academia, and community to redesign health.